Energetic N‐Trinitroethyl‐Substituted Mono‐, Di‐, and Triaminotetrazoles. Issue 33 (21st June 2013) - Zhang, Qinghua; Zhang, Jiaheng; Parrish, Damon A.; Shreeve, Jean'ne M.
Abstract A series of dense energetic N‐trinitroethyl‐substituted mono‐, bis‐, and tri‐5‐aminotetrazoles were obtained by reacting primary amines with in situ generated cyanogen azide, followed by the trinitroethyl functionalization that involves a condensation of a hydroxymethyl intermediate (prepared by a reaction with formaldehyde) with trinitromethane. These compounds were fully characterized by using multinuclear NMR spectroscopy, IR, elemental analysis, differential scanning calorimetry (DSC), and, in one case with 9, with single‐crystal XRD analysis. The heats of formation for all compounds were calculated with Gaussian 03 and then combined with experimental densities to determine the detonation pressures (P) and velocities (Dv) of the energetic materials. Interestingly, most of them exhibited high density, good thermal stability, acceptable oxygen balance, positive heat of formation, low impact sensitivity, and excellent detonation properties, which highlighted their practical application potentials as a fascinating class of highly energetic materials.